Navigating Academic Writing: EFL Students Teachers’ Challenges and Solutions - Nawangsih, Nawangsih; Fajaryani, Nunung; Abrar, Mukhlash (Edukasi, 2024)
At the university level, mastering academic writing skills is a significant concern for students. However, in EFL contexts, academic writing is considered a challenging skill. The purposes of this research were to investigate challenges faced by EFL student teachers and how they overcome those challenges. The theoretical framework of cultural capital was used to guide the research. The research employed qualitative research design with a case study approach. Purposive sampling was used to select the participants. There were 8 participants voluntarily agreed to participate in this research. In collecting the data, the researchers used semi-structured in-depth interviews and document analysis. Thematic analysis was used to analyze the data. The results of the research revealed 1) six major themes of challenges including mechanics of writing, socio-cultural, psychological aspects, critical thinking skills, unity, and literature review writing. 2) the EFL student teachers used strategies to overcome their academic writing challenges that classified into metacognitive strategies, cognitive strategies, and social strategies.